A Study on Consumers’ Willingness to Pay for Remanufactured Products: A Study Based on Hierarchical Regression Method - Chen, Yao; Wang, Jinfei; Yu, Yinglei (Frontiers in Psychology, 2019)
Remanufactured Product, as one of the low-carbon products, is turned out to be more valuable and an increasing number of countries attach much importance to it. However, the low willingness of Chinese consumers to pay for the remanufactured products makes things go harder in the Chinese market. Our research, based on the form of questionnaire, attempts to explore the factors that affect the willingness of consumers to pay for the remanufactured products though Hierarchical regression analysis. The results show that population variables (age, education, occupation and income), individual subjective variables (environmental awareness, old-product preference and reliance on Made in China) and product perception variables (perceived quality risk of MP4, face issue and environmental effect of product) have marked influences on the willingness to pay for the remanufactured products.